Guide to hedge funds: what they are, what they do, their risks, their advantages - Coggan, Philip (London, 2011)
This book gives a thorough but concise overview of the hedge fund industry, its significance, and its major players. Accessible to anyone interested in finding out more about hedge funds"--Provided by publisher.
Keywords: Hedge funds